Juvenile hyaline fibromatosis - Jayashree Krishnamurthy; Bibhas Saha Dalal; Sunila; Gubanna V Manjunath (Wolters Kluwer Medknow Publications, 2011)
Juvenile hyaline fibromatosis is a rare, autosomal-recessive disease characterized by papular and nodular skin lesions, gingival hyperplasia, joint contractures and bone involvement in variable degrees. It is a connective tissue disorder with aberrant synthesis of glycosaminoglycans by fibroblasts. We report a 5-year-old female born of first-degree consanguineous marriage who presented with multiple, recurrent, painless, variable-sized nodules. Fine needle aspiration cytology smears and the subsequent histopathological examination from the nodules showed benign spindle cells in a Periodic acid Schiff-positive myxoid background. The disease has a relentlessly progressive course, with most patients surviving only up to the 4 th decade. As of now, there is no specific treatment for this disorder. Genetic counseling is essential to explain to parents about a 25% chance of having a diseased baby in any pregnancy. With the gene being mapped recently, techniques for antenatal diagnosis are likely to be established.